Implications of Separation of Dispute Resolution of Election Results in Indonesia - Siboy, Ahmad (Fakultas Hukum Universitas Hang Tuah, 2025)
Presidential, regional, and village head elections are forms of elections that stand on the principle of popular sovereignty. However, in terms of resolving disputes over election results, the pattern of resolution of the three types of elections is different from one another and does not show a pattern of handling that is fair and in harmony with one another. This research aims to explain the differences in the handling patterns of the settlement of disputes over the results of the Presidential Elections, Regional Head Elections, and Pilkades (Vllage Head Elections) and the implications caused. This research used normative juridical research with a conceptual approach, legislation, and case approach. The results showed that the Constitutional Court adjudicated the Presidential Election, the Regional Head Election was adjudicated by a Special Judicial Body, while the Pilkades did not have a judicial process but a settlement process carried out by the Regent, even though the Regent is an executive official or political position. The different patterns of settlement indicate that: (i) there is a disregard for the similar characteristics of disputes over election results and the handling of disputes over Pilkades results as a settlement process that is ruled out considering that there is no judicial institution authorized to adjudicate until the absence of procedural law. (ii) Prioritization. When the election result dispute resolution institution is separated into three different institutions, it certainly also reveals the different treatment of each result dispute resolution and ignores the principle of simple justice.